Phase segregation due to ion migration in all-inorganic mixed-halide perovskite nanocrystals - Huichao Zhang; Xu Fu; Ying Tang; Hua Wang; Chunfeng Zhang; William W. Yu; Xiaoyong Wang; Yu Zhang; Min Xiao (Nature Communications, 2019)
Mixed-halide perovskites possess excellent semiconductor properties but suffer severely from notorious light-induced phase segregation effect. Here Zhang et al. employ simple photoluminescence measurements to link the effect to the local electric field induced ion migration process.